Letter (copy) : Goods for Spain - Tewson, Vincent
029-0181-001 HVT/EK/656. Secretary's. 8th April, 1937. Mr. D. Fernandez-Shaw, The Commercial Attache to the Spanish Embassy, 21, Cavendish Square, London, W.1. Dear Sir, GOODS FOR SPAIN. Very many thanks for your letter of the 6th instant promising that you will let us know as soon as you hear of a steamer leaving for Bilbao. I have been thinking over this question and I am wondering if matters will be facilitated in any way if we were to think in terms of either Santander or Gijon. I appreciate that the present circumstances in the North West of Spain make matters extremely difficult, but I would like to find the earliest possible way of rendering assistance in the manner suggested. As the two further places that I have mentioned are not in quite such a difficult position from a military point of view as Bilbao, I am mentioning them just in the hope that there may be some boat leaving for one or other of these places which may not be going to Bilbao. What do you think? Yours faithfully, Assistant Secretary. 292/946/29/181